Non-flat Friedmann-Lemaitre-Robertson-Walker universe with Barrow holographic dark energy - Mahanta, Chandra Rekha; Medhi, Joy Prakash; Mahanta, Rajashree (East European Journal of Physics, 2024)
In this paper, we study a non-flat Friedmann-Lemaitre-Robertson-Walker (FLRW) universe filled with cold dark matter and Barrow holographic dark energy. We assume the Hubble horizon as IR cutoff and the scale factor to obey a hybrid expansion law to construct a cosmological model within the framework of General Relativity. The physical and geometrical properties of the model are discussed by studying the evolution of various parameters of cosmological importance. The behaviour of the dark energy equation of state parameter  wDE is also studied for both interacting and non-interacting Barrow holographic dark energy. We observe that the Barrow exponent ∆ significantly affects the dark energy equation of state parameter which in turn exhibits the behaviour of quintessence and phantom dark energy. The evolution of the jerk parameter is also studied.